2020
DOI: 10.3390/e22121334
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Information in the Spiking–Bursting Stochastic Model

Abstract: Integrated information has been recently suggested as a possible measure to identify a necessary condition for a system to display conscious features. Recently, we have shown that astrocytes contribute to the generation of integrated information through the complex behavior of neuron–astrocyte networks. Still, it remained unclear which underlying mechanisms governing the complex behavior of a neuron–astrocyte network are essential to generating positive integrated information. This study presents an analytic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, scholars proposed several digital implementations of astrocytic dynamics [22] and neuron-astrocyte interaction [23], [24]. In our previous works, we investigated how the astrocyte-induced dynamic coordination in the neuronal ensembles [25], [26] induces the generation of integrated information sets [27], [28], [29]. Moreover, we showed that a biologically inspired SNAN can implement the multiitem short-term memory [30], [31].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, scholars proposed several digital implementations of astrocytic dynamics [22] and neuron-astrocyte interaction [23], [24]. In our previous works, we investigated how the astrocyte-induced dynamic coordination in the neuronal ensembles [25], [26] induces the generation of integrated information sets [27], [28], [29]. Moreover, we showed that a biologically inspired SNAN can implement the multiitem short-term memory [30], [31].…”
Section: Related Workmentioning
confidence: 99%
“…The list of functions handled by the astrocytic cells keeps getting updated and revised quite frequently [15][16][17][18][19][20]. Several studies discuss the role of astrocytes in the perception of sensory stimuli [21][22][23][24], spatio-temporal coordination of neural network signaling [25][26][27][28][29][30], information processing, and cognitive functions [31][32][33]. A growing number of arguments are accumulating in favor of the theory of continuity and joint coordinated activity of neuron-astrocyte functional networks [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…All these findings in molecular biology pave the way for a better understanding of the information processing in neuronastrocyte circuits and the formation of cognitive functions. Very recently, mathematical and computational approaches have been used to investigate the contribution of astrocytes to the organisation of spatial and temporal synchronization in neural networks [29][30][31][32], formation of short-term memory [33][34][35][36][37][38] and generation of integrated information in neuronal ensembles [39][40][41][42], which takes a step further to the understanding of the intelligence arising from the nervous system. Nowadays, a widely accepted fact is that astrocytes play an active role in various types of memory and the memory improvement may be related to the change in the astrocyte density [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%